Cell reprogramming and neuronal differentiation applied to neurodegenerative diseases: Focus on Parkinson's disease - Wenker, Shirley Denise (2015)
Adult cells from patients can be reprogrammed to induced pluripotent stem cells (iPSCs) which successively can be used to obtain specific cells such as neurons. This remarkable breakthrough represents a new way of studying diseases and brought new therapeutic perspectives in the field of regenerative medicine. This is particular true in the neurology field, where few techniques are amenable to study the affected tissue of the patient during illness progression, in addition to the lack of neuroprotective therapies for many diseases. In this review we discuss the advantages and unresolved issues of cell reprogramming and neuronal differentiation. We reviewed evidence using iPSCs-derived neurons from neurological patients. Focusing on data obtained from Parkinson's disease (PD) patients, we show that iPSC-derived neurons possess morphological and functional characteristics of this disease and build a case for the use of this technology to study PD and other neuropathologies while disease is in progress. These data show the enormous impact that this new technology starts to have on different purposes such as the study and design of future therapies of neurological disease, especially PD.